The Implementation of Housing Development Licensing and Non-Licensing Policies for Low Income Communities of Sukabumi City - Siti Syadzalia Azmila; Andi Mulyadi; M. Rijal Amirulloh (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
The purpose of the study was to determine the process of implementing licensing and non-licensing housing development which was held to meet housing needs for low-income people. The method in this study uses a descriptive research method with a qualitative approach. Data collection techniques using interview techniques, observation, and documentation related to the research. The data analysis technique in this study was carried out qualitatively. This study uses five dimensions of policy implementation from Van Meter Van Horn. Based on the results of research that has been carried out by researchers regarding the Implementation of Licensing and Non-licensing Implementation Policies for housing development for low-income communities in Sukabumi City as a whole it has been going well and optimally, but there are some things that are still not going well. Social and economic conditions have a good effect on the community, especially people with low incomes, previously they did not have a home and now have a home. Another thing is the decrease in investors in investing in the Sukabumi City area caused by the global pandemic which has an impact on all aspects.